Evaluation of the prescribed drugs to elderly in a tertiary healthcare center for possible drug interactions with investigational drugs for covid-19 treatment - Yogendra Keche; Nitin Gaikwad; Suryaprakash Dhaneria; Apoorva Joshi (Wolters Kluwer Medknow Publications, 2020)
Objective: Earlier identifying drug interactions may help in risk reduction in elderly patients. Methods: Drug prescription data of 212 elderly patients of tertiary health care center had been analyzed for possible drug interactions with investigational drugs for COVID-19 treatment. Drug interaction had been checked from Stockley's Drug Interaction 2019 and Martindale the Complete Drug Reference 2017 and standard reference books of Pharmacology. Findings: Different types of drugs prescribed in the elderly were 260 and out of which 68 (26.36%) were in the category of fixed-dose combinations. Around 150 (70.75%) elderly patients were having one or more associated comorbidities. Thirty-five drugs prescribed to elderly had been found to cause drug interaction with investigational drugs for COVID-19. Possible drug interactions are mediated through CYP3A4 (eighteen patients), CYP2D6 (seven patients) isoenzymes, or P glycoproteins transporters (three patients). Conclusion: Possible drug interactions predicted in this study suggested need for modification of dose of drug or watchfulness for adverse effects. If these drug interactions are considered beforehand, complications can be prevented on account of these drug interactions in elderly who are suffering from COVID-19.